Solusi Pencegahan Korupsi dalam Al-Qur’an - Suhartawan, Budi (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
Corruption has become a structural, cultural and personal problem. It is even categorized as a major crime that has created dangerous problems and threats because it can damage the stability and security of the state and also the moral decline of the people. This research aims to uncover and analyze how corruption is seen in the Qur'an, understand what types of corruption are, what are the main factors of corrupt behaviour and what and how the Qur'an offers solutions regarding corruption prevention. The method used in this study is a thematic-based library method that focuses on reviewing the literature related to the discussion theme. The results of this study are that the Qur'an provides solutions to prevent corruption by: first, building civil society, second, improving oneself through identity identification, third, building Good Governance (good governance), and actualizing values. tazkiyatun nafs.